2017
DOI: 10.1002/adv.21839
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐enzymatic synthesis of dendronized polymers for cyanine dye encapsulation

Abstract: Cyanine 3 is an amphiphilic fluorescent dye used in optical imaging, bioengineering, and for cellular internalization. However, the applications of the dye are limited due to its poor aqueous stability, aggregation tendency, and lack of selectivity. To address these issues, we have developed PEG and azidotriglycerol based dendronized polymers using Novozym 435 as a biocatalyst under solvent free conditions. The resulting polymer having azido and hydroxyl functionalities available in the backbone were further g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The CMC of the pentablock was similar in water and in physiological saline solution (i.e., NaCl 0.15 M), with a value of about 30 μg·mL –1 (Figure , left). It is interesting to note that, besides strong absorbance increase, the encapsulation of the dye provoked a shift of the λ max toward higher wavelengths as a result of environmental change of the dye (i.e., from 678 nm in aqueous medium to 688 nm in micelle core, see arrows in Figure , right). The CMC was also determined by the DLS dilution method , and was in very good accordance with that obtained with the Cy5.5 probe (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The CMC of the pentablock was similar in water and in physiological saline solution (i.e., NaCl 0.15 M), with a value of about 30 μg·mL –1 (Figure , left). It is interesting to note that, besides strong absorbance increase, the encapsulation of the dye provoked a shift of the λ max toward higher wavelengths as a result of environmental change of the dye (i.e., from 678 nm in aqueous medium to 688 nm in micelle core, see arrows in Figure , right). The CMC was also determined by the DLS dilution method , and was in very good accordance with that obtained with the Cy5.5 probe (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…%) mixed with Cy5.5 (3.3 µg•mL −1 ) led to significant solubilization of the dye (through micellar encapsulation) while the dye remained mostly insoluble in the case of the control P(NIPAAm-co-PEGMA) copolymer, as shown by UV-visible absorption (Figure 3B). In addition to strong absorbance increase, the encapsulation of the dye provoked a shift of the λ max toward higher wavelengths as a result of environmental change of the dye [26] (i.e., from 677 nm in aqueous medium to 690 nm in micelle core), supporting that Cy5.5 was located in the hydrophobic core (PLA) of the micelles. Together with DLS, this clearly showed that PLA in the copolymer induces amphiphilic character for PLA-b-P(NIPAAm-co-PEGMA) and thus micelle formation.…”
Section: Aqueous Solution Properties Of the Copolymermentioning
confidence: 88%